Experimental investigations on the hydrodynamics of a multi-body floating aquaculture platform exposed to sloping seabed environment - Zhao, Yunpeng; Xie, Sida; Ma, Chao (Frontiers in Marine Science, 2022)
The coastal area near islands has become a key area for aquaculture because of the long offshore distance and suitable wave conditions. There is a topographic change near the islands, and the reflected waves generated by the topography modify the wave field in the aquaculture area, which may cause structural damage to the offshore net cage. Most studies on the hydrodynamic characteristics of aquaculture structures do not consider the effects of topography. Therefore, we investigated the hydrodynamic characteristics and wave field of a multi-body floating aquaculture platform under the influence of sloping seabed by leveraging a physical model approach. The results show that the low-frequency component of the surge motion of the cage on the weather side increases significantly under the influence of sloping seabed. However, the heave and pitch motions change slightly. Considering the presence of the sloping seabed, the wave elevations inside cages have been changed too., The wave breaking inside the cage on the weather side becomes more evident when the incident wavelength is equal to the width of the cage. And its wave response gradually shifts from wave frequency to high frequency. Regarding the cage on the lee side, the wave response inside it is positively correlated with the incident wavelength. The results of this study provide a reference for the design and optimization of aquaculture structures anchored near islands.